NIR induced self-healing electrical conductivity polyurethane/graphene nanocomposites based on Diels−Alder reaction. (28th March 2018) - Lin, Changhong; Sheng, Dekun; Liu, Xiangdong; Xu, Shaobin; Ji, Fance; Dong, Li; Zhou, Yan; Yang, Yuming
Abstract: In this work, a crosslinker terminal maleimide groups (EDM) has been synthesized and was used in reactions with the pendant furan groups of polyurethane (PUE) to prepare the self-healing electrically conductive composites based on Diels-Alder reaction, and Ag nanowires (AgNWs) as the conductive network inlaid in the surface layer of the polymer matrix layer. Inspired by the graphene-based materials for its versatility in both material and chemical properties, and we present a new synthetic strategy for the preparation of functional graphene nanosheets with DA group that can be employed in the self-healing polyurethane system. To our best knowledge, it hasn't been reported yet the structure graphene oxide materials (rmGO) in any systems. The rmGO served as fillers to reinforce the composites and would participated in the DA reactions. The excellent NIR light-induced self-healing property of prepared composites was realized through the photo-thermal effect of rmGO. The composite is capable of both structural and electrical healing via NIR irradiation. The injured samples can be locally repaired with high precision and efficiency without an obvious influence on those uninjured parts. The underlying polymer matrix can reform via the dynamic dissociation/recombination of Diels-Alder bonds to bring the separated areas of the AgNWs layer into contact to restore the conductivity. The NIR light-induced self-healing electrically conductive composites have wide potential for many fields, e.g., soft robots, flexible devices, and health-monitoring. Graphical abstract: The electrically conductive polyurethane with reduced maleimide functionalization graphene Oxide based on Diels-Alder (DA) reaction displayed a NIR-induced self-healing property. Highlights: The rmGO can improve the mechanical properties of the composites based on Diels-Alder (DA) reaction. The composites can be healed via heating and NIR irradiation. Self-healing electrically conductive composites could be healed highly efficiency.